Reply to: MoCA Test Mandatory Training and Certification: What Is the Purpose?. Issue 2 (2nd December 2019) - Borson, Soo; Sehgal, Mandi; Chodosh, Joshua
Abstract : This letter comments on the letter by Ziad Nasreddine .